The Relationship of Pregnancy Distance and Mother's Knowledge on The Incident of Stunting in Toddler - Andriani, Rika; Rosita, Erlia; Bancin, Ratnawati; Wiguna, Rizaldi Nanda; Marhamah, Epi (Griya Widya: Journal of Sexual and Reproductive Health, 2023)
Background: Stunting is a nutritional problem in developing countries, especially in the first 1000 days of life, as can be seen from chronic growth and development disorders in children. The government's attention is focused on dealing with stunting in Indonesia, even though there has been a decline in the stunting rate in 2021, namely 24.4 and in 2022, namely 21.6%, but it is still far from the target. Method: This type of research is quantitative with a cross sectional design. The sample in this study amounted to 114 respondents and the sampling technique used stratified random sampling. Result: The results of the research show that there is a relationship between pregnancy distance and maternal knowledge on the incidence of stunting in toddlers with a p-value of 0.000. Implication: Stunting cases must be resolved seriously from all levels, starting from increasing mothers’ knowledge regarding fulfilling maternal nutrition during pregnancy, support from husbands/families, health workers with health education for mothers and the government as well as issuing policies to reduce stunting rates and programs that have been implemented then controlled maximally until it matches the target.